Preventing governance breakdown in the EU's southern neighbourhood: fostering resilience to strengthen security perceptions. Issue 7 (3rd October 2021) - Stollenwerk, Eric
ABSTRACT: To what extent does societal resilience help to prevent governance breakdown? The EU's southern neighbourhood has been troubled by multiple security risks in recent years. The security situation of many citizens is uncertain and local populations frequently feel insecure, an indication of governance breakdown. Resilience has become a new focus in preventing a breakdown of governance. Yet, the extent to which resilience can help prevent governance breakdown remains unclear. Building on original survey data from Libya and Tunisia this study contributes empirical evidence to the debate. The article shows that limited statehood and order contestation do not necessarily lead to a breakdown of governance. Although both risks affect Tunisia and Libya to different degrees none of them are strongly correlated with the security perceptions of local populations. Additionally, resilience is key in preventing governance breakdown. Social trust and the legitimacy of governance actors are two main sources of resilience helping to prevent a breakdown of governance. Moreover, resilience has divergent effects on different dimensions of security governance breakdown. While resilience has stronger effects on national security perceptions, local security considerations are partly driven by other factors such as individuals' economic resources.